2004
DOI: 10.1152/ajprenal.00420.2003
|View full text |Cite
|
Sign up to set email alerts
|

Real-time imaging of renin release in vitro

Abstract: lease from juxtaglomerular granular cells is considered the ratelimiting step in activation of the renin-angiotensin system that helps to maintain body salt and water balance. Available assays to measure renin release are complex, indirect, and work with significant internal errors. To directly visualize and study the dynamics of both the release and tissue activity of renin, we isolated and perfused afferent arterioles with attached glomeruli dissected from rabbit kidneys and used multiphoton fluorescence ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
106
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(110 citation statements)
references
References 29 publications
2
106
0
2
Order By: Relevance
“…4B). Consistent with this result, plasma renin measurements (27,28) revealed that Olfr78 −/− mice fed a standard chow diet rich in plant polysaccharides have significantly lower plasma renin levels than wild-type mice fed the same diet ( Fig. 4C, P < 0.05).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…4B). Consistent with this result, plasma renin measurements (27,28) revealed that Olfr78 −/− mice fed a standard chow diet rich in plant polysaccharides have significantly lower plasma renin levels than wild-type mice fed the same diet ( Fig. 4C, P < 0.05).…”
Section: Resultssupporting
confidence: 79%
“…The disappearance of quinacrine over time was measured as an index of renin release (26,27). Addition of 10 mM propionate to the bathing solution of JGA/glomeruli from wild-type mice resulted in a decrease in cell-associated quinacrine fluorescence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the implications from this work and the autoradiographic data are that aliskiren may provide an unusual example in which an inhibitor incorporates into its (still intracellular) target even before the latter is secreted. In this case, (pro)renin would be secreted from JG cells to the plasma or the tubulo-interstitium 103 in an already inhibited state. The renin activity in this (pro)renin-aliskiren complex would be inhibited: this renin (or prorenin, which may undergo activation at tissue sites) could not cleave Aogen, and the tissue and systemic RAAS cascades would not be activated.…”
Section: Aliskiren Localizes In the Kidneymentioning
confidence: 99%
“…Multiphoton florescence imaging has recently made it possible to visualize and study the dynamics of both the release and tissue activity of renin in isolated and perfused afferent arterioles with attached glomeruli dissected from rabbit kidneys. Supportive of renin release into the interstitium, was the observation that quinacrine-labeled renin-granules disappeared while there was a simultaneous increase in renin activity of fluid around granular cells of the M a n u s c r i p t perfused afferent arteriole (Peti-Peterdi et al, 2004. In addition, under most circumstances interstitial renin concentration is much higher than that of the circulating blood.…”
Section: Renin In Different Renal Compartmentsmentioning
confidence: 99%